Alleviation of hippocampal necroptosis and neuroinflammation by NecroX-7 treatment after acute seizures - Roh, Yihyun; Lee, Su Bin; Kim, Minseo; Kim, Mi-Hye; Kim, Hee Jung; Cho, Kyung-Ok (Frontiers in Pharmacology, 2023)
Temporal lobe epilepsy (TLE) is one of the most common neurological disorders, but still one-third of patients cannot be properly treated by current medication. Thus, we investigated the therapeutic effects of a novel small molecule, NecroX-7, in TLE using both a low [Mg2+]o-induced epileptiform activity model and a mouse model of pilocarpine-induced status epilepticus (SE). NecroX-7 post-treatment enhanced the viability of primary hippocampal neurons exposed to low [Mg2+]o compared to controls in an MTT assay. Application of NecroX-7 after pilocarpine-induced SE also reduced the number of degenerating neurons labelled with Fluoro-Jade B. Immunocytochemistry and immunohistochemistry showed that NecroX-7 post-treatment significantly alleviated ionized calcium-binding adaptor molecule 1 (Iba1) intensity and immunoreactive area, while the attenuation of reactive astrocytosis by glial fibrillary acidic protein (GFAP) staining was observed in cultured hippocampal neurons. However, NecroX-7-mediated morphologic changes of astrocytes were seen in both in vitro and in vivo models of TLE. Finally, western blot analysis demonstrated that NecroX-7 post-treatment after acute seizures could decrease the expression of mixed lineage kinase domain-like pseudokinase (MLKL) and phosphorylated MLKL (p-MLKL), markers for necroptosis. Taken all together, NecroX-7 has potential as a novel medication for TLE with its neuroprotective, anti-inflammatory, and anti-necroptotic effects.